Angiotensin II-Regulated Autophagy Is Required for Vascular Smooth Muscle Cell Hypertrophy - Mondaca-Ruff, David; Riquelme, Jaime A.; Quiroga, Clara; Norambuena-Soto, Ignacio; Sanhueza-Olivares, Fernanda; Villar-Fincheira, Paulina; Hernández-Díaz, Tomás; Cancino-Arenas, Nicole; San Martin, Alejandra; García, Lorena; Lavandero, Sergio; Chiong, Mario (Frontiers in Pharmacology, 2019)
Hypertension is a disease associated to increased plasma levels of angiotensin II (Ang II). Ang II can regulate proliferation, migration, ROS production and hypertrophy of vascular smooth muscle cells (VSMCs). However, the mechanisms by which Ang II can affect VSMCs remain to be fully elucidated. In this context, autophagy, a process involved in self-digestion of proteins and organelles, has been described to regulate vascular remodeling. Therefore, we sought to investigate if Ang II regulates VSMC hypertrophy through an autophagy-dependent mechanism. To test this, we stimulated A7r5 cell line and primary rat aortic smooth muscle cells with Ang II 100 nM and measured autophagic markers at 24 h by Western blot. Autophagosomes were quantified by visualizing fluorescently labeled LC3 using confocal microscopy. The results showed that treatment with Ang II increases Beclin-1, Vps34, Atg-12–Atg5, Atg4 and Atg7 protein levels, Beclin-1 phosphorylation, as well as the number of autophagic vesicles, suggesting that this peptide induces autophagy by activating phagophore initiation and elongation. These findings were confirmed by the assessment of autophagic flux by co-administering Ang II together with chloroquine (30 µM). Pharmacological antagonism of the angiotensin type 1 receptor (AT1R) with losartan and RhoA/Rho Kinase inhibition prevented Ang II-induced autophagy. Moreover, Ang II-induced A7r5 hypertrophy, evaluated by α-SMA expression and cell size, was prevented upon autophagy inhibition. Taking together, our results suggest that the induction of autophagy by an AT1R/RhoA/Rho Kinase-dependent mechanism contributes to Ang II-induced hypertrophy in VSMC.